"I wanted information": navigating breast Cancer and its treatment in Lima, Peru - Brittany C. Fields; Rachel M. Morse; Emma Ortega; Kristen Waterfield; Bryn A. Prieto; Richard Oberhelman; Valerie A. Paz-Soldán (BMC, 2023)
Abstract Background Breast cancer impacts millions of people worldwide, and in Peru, breast cancer is the most common cause of cancer related death among women. Breast cancer treatment is physically and emotionally burdensome and challenging for patients. Methods In-depth interviews were conducted with 14 female breast cancer patients and survivors in Lima, Peru. The interviews explored four main themes: the women's emotional experiences, coping mechanisms, resources available or needed, and advice for newly diagnosed breast cancer patients. Results Respondents described a tremendous lack of informational support during and after diagnosis and treatment and requested more of this support from health professionals. Social support groups were helpful to participants; however, these forms of support were not available to all participants. Emotional and esteem support seemed amply received from family and friends, faith organizations, and fellow cancer patients. Participants experienced a range of emotions upon diagnosis and during treatment including fear, anxiety, difficulty accepting bodily changes, loneliness, and denial. Conclusion Breast cancer and its treatment can be a long, emotional journey; more extensive forms of informational support could help patients cope with this process.